Systematic Review and Meta-analysis of Conventionally Fractionated Concurrent Chemoradiotherapy versus Altered Fractionation Radiotherapy Alone in the Definitive Management of Locoregionally Advanced Head and Neck Squamous Cell Carcinoma. Issue 1 (January 2016) - Gupta, T.; Kannan, S.; Ghosh-Laskar, S.; Agarwal, J.P.
Abstract: Aims: Treatment intensification either by using concurrent chemoradiotherapy (CCRT) or altered fractionation radiotherapy (AFRT) improves outcomes of locoregionally advanced head and neck squamous cell carcinoma (HNSCC). The superiority of one approach over the other, however, remains to be firmly established. The aim of the present study was to compare outcomes of CCRT versus AFRT in the definitive non-surgical management of locoregionally advanced HNSCC for evidence-based decision making. Materials and methods: An electronic search of Medline via PubMed was conducted with no language, year, or publication status restrictions. The Cochrane Central Register of Controlled Trials (CENTRAL) and Database of Abstracts of Reviews of Effectiveness (DARE) were also searched electronically. Only randomised controlled trials assigning HNSCC patients randomly to conventionally fractionated CCRT or AFRT alone were included. Data were extracted independently by two reviewers and pooled using the Cochrane methodology for meta-analysis and expressed as a hazard ratio with 95% confidence intervals. Overall survival was the primary outcome of interest, whereas disease-free survival, locoregional control and toxicity were secondary end points. Results: Five randomised controlled trials (involving 1117 patients and 627 deaths) directly comparing conventionally fractionated CCRT with AFRT alone were included. The risk of bias in included studies was low for efficacy outcomes, but high for toxicity outcomes. The overall pooled hazard ratio of death was 0.73 (95% confidence interval = 0.62–0.86), which significantly favoured conventionally fractionated CCRT over AFRT alone ( P < 0.0001). Similarly, disease-free survival (hazard ratio = 0.79, 95% confidence interval = 0.68–0.92; P = 0.002) and locoregional control (hazard ratio = 0.71, 95% confidence interval = 0.59–0.84; P < 0.0001) were significantly improved with CCRT. There were no significant differences in the incidence of severe acute toxicity (dermatitis and mucositis) between the two approaches of treatment intensification. Late xerostomia was significantly increased with CCRT. Significant haematological toxicity and nephrotoxicity were seen exclusively with chemotherapy. Conclusion: There is moderate quality evidence that conventionally fractionated CCRT improves survival outcomes compared with AFRT alone in the definitive radiotherapeutic management of locoregionally advanced HNSCC. No form of acceleration can potentially compensate fully for the lack of concurrent chemotherapy.